2002
DOI: 10.1080/15216540216039
|View full text |Cite
|
Sign up to set email alerts
|

Mood‐Enhancing Antidepressant St. John's Wort Inhibits the Activation of Human Immunodeficiency Virus Gene Expression by Ultraviolet Light

Abstract: Summary Ultraviolet (UV) radiation is a potent activator of the human immunodeficiency virus (HIV) gene expression in a HeLa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…While PPME-PDT induces NF-kB activation in various cell lines (Matroule and Piette, 2000a;Volanti et al, 2002), no NF-kB activation is observed upon HYP-PDT (Hendrickx et al, 2003). In addition, HYP has been described as an NF-kB inhibitor in HeLa and T10 cells after UVB, PMA or TNF-a stimulation (Bork et al, 1999;Taher et al, 2002). This was confirmed in this work by the absence of p38, JNK and Erk-1,2 activation in both HeLa and T24 cells photosensitized by PPME.…”
Section: Discussionmentioning
confidence: 99%
“…While PPME-PDT induces NF-kB activation in various cell lines (Matroule and Piette, 2000a;Volanti et al, 2002), no NF-kB activation is observed upon HYP-PDT (Hendrickx et al, 2003). In addition, HYP has been described as an NF-kB inhibitor in HeLa and T10 cells after UVB, PMA or TNF-a stimulation (Bork et al, 1999;Taher et al, 2002). This was confirmed in this work by the absence of p38, JNK and Erk-1,2 activation in both HeLa and T24 cells photosensitized by PPME.…”
Section: Discussionmentioning
confidence: 99%
“…John's wort potently inhibits UV-induced activation of HIV gene expression in stably transfected HIVcat/HeLa cells, in a dose-dependent manner. Since hypericin is known to exhibit a similar inhibitory property, it is likely to be the active constituent of St. John's wort (Taher et al, 2002).…”
Section: Polyphenolsmentioning
confidence: 99%
“…Hypericin is a secondary metabolite of Hypericum perforatum, which is effective against depression and anxiety and active against several viruses, including cytomegalovius, human papillomavirus, papillomavirus, and herpes [20][21][22] . Cell cultures of H. perforatum provide an alternative way to produce hypericin owing to the scarcity of H. perforatum in the world and extremely low levels of the compound in the plant.…”
mentioning
confidence: 99%